LANGUAGE POLICY IN THE PORTUGUESE REPUBLIC: FROM UNIFICATION TO MULTICULTURALISM (Coordinates of Public Administration, 2026)
The article provides a comprehensive analysis of the language policy of the Portuguese Republic as an example of a state that balances between preserving the normative purity of a single state language and the challenges of globalization, migration, and the protection of autochthonous minorities; It is shown that the language policy of Portugal is a unique object of study, as it goes far beyond national borders; it is found that the Portuguese language is pluricentric - it has two main standards (European and Brazilian) and is official in 9 countries of the world; a study was conducted on the evolution of Portugal's language policy, analyzing the key stages of the transition from strict linguistic unification to a modern model that takes into account the principles of multiculturalism and inclusion; The object of the study was the regulatory framework and sociolinguistic strategies of the Portuguese state in the 20th–21st centuries; key regulatory acts, statistical data, and works of foreign and domestic researchers were analyzed; special attention is paid to the phenomenon of Lusophony, the status of the Miranda and Barranquilla languages, and contemporary problems related to the Orthographic Agreement and the digital expansion of the Brazilian variant of Portuguese; It has been established that for a long time, Portugal's language policy was based on the ideology of «one nation – one language», which was especially characteristic of the period of the «New State» (Estado Novo); It was found that at that time the Portuguese language served as a tool for consolidating the dictatorial regime of Salazar and leveling regional differences; it is proven that the democratization of society after 1974 and Portugal's accession to the EU led to a revision of the priorities of its language policy; It is shown that modern Portugal has built a fairly flexible model of state language policy, which researchers often call «soft power» or «inclusive language planning», which balances between preserving the Portuguese language as the foundation of the nation and recognizing the realities of a globalized world.